Fundamental nature of chemical bonding from the novel Fragment Atom Localised Delocalised and Interatomic (FALDI) electron density decomposition scheme: A theoretical study - Cukrowski, Ignacy (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.